Pengembangan AR (Augmented Reality) Mangrove Berbasis Website Pada Materi Keanekaragaman Hayati - Muhammad Aris Mulya Firmansyah; Dwi Ratnasari; Mahrawi Mahrawi; Indria Wahyuni (Jurnal Inovasi Pendidikan dan Sains, 2022)
This study aims to develop web based Augmented Reality (AR) learning media on mangrove biodiversity (RovAR) materials, and assess the feasibility of media from experts and samples. This study is a Research and Development study. The research sample consisted of 20 students of class X science. The RovAR learning media development process was carried out by analyzing various problems and potential media development innovations obtained from schools and literature studies, collecting initial data to support the media development process, designing media products by making system architecture designs, storyboards, and visualizing system designs. The applications used are Blender, Sketchfab.com, Affinity Designer, Zapwork Designer, Zapwork Studio and Wordpress.com. The results of the expert test analysis showed that the average score from the material expert team was 72% and from the media expert team it was 82.2% in the good media category. The results of the students' response test showed that the media feasibility interpretation score from the use of the SUS instrument is 80.125, which means that RovAR is a good medium. The students accept the RovAR learning media as a suitable medium to be used to help them understand mangrove material on biodiversity material.